An Applicability of Vyalov’s equations to ice wall strength estimation (Fracture and Structural Integrity, 2020)
A simple analytical relations are commonly used in engineering practice to calculate ice wall thickness. One of them is Vyalov’s relation that takes into account the features of a real technological process of tubing lining and the inelastic deformation associated with frozen soil creep. An estimation of applicability and margin of safety of this equation is an issue of engineering mechanics. In this paper, we propose a mathematical model for description of ice wall deformation under natural external loading and present the results of the computational experiments in which an optimal thickness for the ice wall is determined. Based on this simulation, we modify the existing analytical relation, which makes it possible to calculate the thickness of an ice wall of unlimited height.
Keywords: ice wall; Vyalov’s equation; frozen soil; mine shaft